Hydro Power 2009 4th International Hydropower Convention: Hydropower for Progress of Nepal - Gangol, Pradeep (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
Not available DOI: 10.3126/hn.v5i0.2497 Hydro Nepal Vol. 5, July 2009 Page:71-73